2015
DOI: 10.1007/s11356-015-4982-9
|View full text |Cite
|
Sign up to set email alerts
|

First inter-laboratory comparison exercise for the determination of anticancer drugs in aqueous samples

Abstract: The results of an inter-laboratory comparison exercise to determine cytostatic anticancer drug residues in surface water, hospital wastewater and wastewater treatment plant effluent are reported. To obtain a critical number of participants, an invitation was sent out to potential laboratories identified to have the necessary knowledge and instrumentation. Nine laboratories worldwide confirmed their participation in the exercise. The compounds selected (based on the extent of use and laboratories capabilities) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The pharmaceutical compounds targeted in this study consisted of eight anticancer drugs, one antidepressant, and one antihypertensive. According to recent studies, C18-based analytical columns are the most suitable and often employed for the analysis of a similar group of compounds in water [ 14 , 30 , 32 ]. In this work, we tested three reversed-phase C18 analytical columns of which one column had additional polar functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmaceutical compounds targeted in this study consisted of eight anticancer drugs, one antidepressant, and one antihypertensive. According to recent studies, C18-based analytical columns are the most suitable and often employed for the analysis of a similar group of compounds in water [ 14 , 30 , 32 ]. In this work, we tested three reversed-phase C18 analytical columns of which one column had additional polar functionality.…”
Section: Resultsmentioning
confidence: 99%
“…The continuous rise of cancer cases has led to the increased use of anticancer drugs and a further increase in their use in the years to come can be foreseen [ 14 , 15 ]. Anticancer drugs (also known as antineoplastics) are generally administered in hospitals and, thus, hospital wastewater is considered as the one of the various routes through which those compounds reach the aquatic environment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,9,10 Most of the reported methods are based on the use of liquid chromatography (LC) coupled with UV spectrophotometry (UV) 11,12,13,14 or mass spectrometry (MS), when there was a need for high selectivity and/or sensitivity. [15][16][17][18][19][20][21][22]23,24,25,26,27,28,29,30,31,32,33,34 Limits of detection 51 In our opinion, ELSD is not recommended for analysing pemetrexed since this molecule is UV-active and ELSD is often less sensitive and selective than the commonly used UV detectors. A methodology including a PP step followed by LC-MS analysis was also developed for the determination of raltitrexed in human plasma with a limit of quantification (LOQ) of 2 ng mL −1 .…”
Section: Antimetabolitesmentioning
confidence: 99%
“…LOD of 1.7 ng mL −1 was reached for the analysis of 5FU in effluents using an SPE-CE-UV method. 106 Gas chromatography (GC) coupled to MS was also used for the analysis of 5FU, 113,114,27 but the time consuming and tedious derivatisation step means low popularity of GC for the analysis of these non-volatile compounds. 2.1.3.…”
Section: Antimetabolitesmentioning
confidence: 99%
“…However, the actual concentration of endoxifen in wastewater and natural water bodies has been poorly documented (Borgatta et al, 2015). The lack of technology and the know-how to measure endoxifen in laboratories are handicaps in order to determine its concentration in wastewater and surface water (Heath et al, 2016;Kovalova, Siegrist, Singer, Wittmer, & McArdell, 2012). Ferrando-Climent, Rodriguez-Mozaz, & Barceló (2013) detected but did not quantify endoxifen in two hospital wastewater samples, while a study by Negreira et al (2014) reported a concentration of 96 ng L -1 of endoxifen in a wastewater effluent sample.…”
Section: General Backgroundmentioning
confidence: 99%